If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8 + -3b = 6 + b + 10 Reorder the terms: -8 + -3b = 6 + 10 + b Combine like terms: 6 + 10 = 16 -8 + -3b = 16 + b Solving -8 + -3b = 16 + b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-1b' to each side of the equation. -8 + -3b + -1b = 16 + b + -1b Combine like terms: -3b + -1b = -4b -8 + -4b = 16 + b + -1b Combine like terms: b + -1b = 0 -8 + -4b = 16 + 0 -8 + -4b = 16 Add '8' to each side of the equation. -8 + 8 + -4b = 16 + 8 Combine like terms: -8 + 8 = 0 0 + -4b = 16 + 8 -4b = 16 + 8 Combine like terms: 16 + 8 = 24 -4b = 24 Divide each side by '-4'. b = -6 Simplifying b = -6
| 9x+39y=0 | | -3b+4=14a-1 | | 120=24n | | 4cos^2-sin^22x=4cos^4x | | 2m+6=24-6m | | 2m+6=24-6 | | x+(0.5x+3)= | | S+11=1+2s | | 7-10v=-9v-9-5v | | 1+3*7= | | 17-4x+2x+9=200 | | 2tan^2x-5tanx+2=0 | | D=205/1*3 | | (3x)(12)/(5)=(2x)(15x)/(20) | | -10g=-8+10 | | 7+3(-1y+3)-2y=15-3 | | 4d=56 | | 3x^2+12-c=0 | | 1+7j=9+9j | | 10=-16t^2+23t+6 | | -5j+17=7j | | -4p+9=-3p | | 8-4(-7x)+3= | | 5x^6=120 | | 5e=75 | | D=300*15 | | -3t+3=-6t | | 3(2x+1)=-5x+3x | | -26x+x^2=-152 | | 5m-8=3m+3 | | 2h+6=10 | | (a^10)/(3a^2) |